Comparison Of Knowledge and Attitude Towards Chat GPT In First and Final-Year Dental Students - Sadia Naureen; Huma Ghazanfar Kiani; Nadia Naureen; Mahnoor Shafique (Journal of Rawalpindi Medical College)
Objective: This study aimed to examine the knowledge and attitude towards Chat-GPT among first and final-year dental students.